[Na4(N5)4(H2O)2]·H2O·2MeOH: a honeycomb-like sodium pentazolate framework with helical chains. Issue 27 (30th June 2022) - Xu, Yuangang; Xu, Ze; Zhang, Xiaopeng; Hou, Tianyang; Lu, Ming
Abstract : A new NaN5 framework, [Na4 (N5 )4 (H2 O)2 ]·H2 O·2MeOH, was synthesized. It features a UNJ-type zeolite topology with double right-handed helical chains constructing enclosed homochiral channels filled with water and methanol molecules. Abstract : A new NaN5 framework, [Na4 (N5 )4 (H2 O)2 ]·H2 O·2MeOH, was synthesized by changing the content of auxiliary ligands. It features a UNJ-type zeolite topology with double right-handed helical chains constructing enclosed channels filled with water and methanol molecules. This work demonstrates the structural diversity of NaN5 frameworks, and their self-assembly can be regulated using appropriate solvents and additives.